2015
DOI: 10.1002/14651858.cd006876.pub4
|View full text |Cite
|
Sign up to set email alerts
|

Electromechanical and robot-assisted arm training for improving activities of daily living, arm function, and arm muscle strength after stroke

Abstract: People who receive electromechanical and robot-assisted arm and hand training after stroke might improve their activities of daily living, arm and hand function, and arm and hand muscle strength. However, the results must be interpreted with caution because the quality of the evidence was low to very low, and there were variations between the trials in the intensity, duration, and amount of training; type of treatment; and participant characteristics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
147
1
12

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 385 publications
(166 citation statements)
references
References 88 publications
6
147
1
12
Order By: Relevance
“…Однако уровень доказательности в сравнении с другими реабилитационными мероприятиями оказался низким. Авторы пришли к выводу, что преимущества изолированной роботизированной терапии не могут быть клинически значимыми [43].…”
Section: мировой опыт применения роботизированных комплексовunclassified
See 1 more Smart Citation
“…Однако уровень доказательности в сравнении с другими реабилитационными мероприятиями оказался низким. Авторы пришли к выводу, что преимущества изолированной роботизированной терапии не могут быть клинически значимыми [43].…”
Section: мировой опыт применения роботизированных комплексовunclassified
“…Устройство HandSOME (Hand Spring Operated Movement Enhancer, США), обеспечивающее захват кистью как мелких, так и крупных предметов, доказало свою ýффективность в качестве реабилитационного метода после инсульта, а также ортопедического комплекса у пациентов с полной утратой функций верхней конечности (рис. 1) [43].…”
Section: мировой опыт применения роботизированных комплексовunclassified
“…Two recent meta-analyses looking at upper limb training found that robotic interventions have a small, but positive effect on motor control and muscle strength post-stroke (Mehrholz, Pohl, Platz, Kugler, & Elsner, 2015;Veerbeek, Langbroek-Amersfoort, van Wegen, Meskers, & Kwakkel, 2017). The impact of these interventions on activities of daily living remains unclear, with authors reporting conflicting conclusions.…”
Section: Considerations On Efficacymentioning
confidence: 99%
“…Robot-mediated therapy after upper limb impairment, because of neurological or orthopedic diseases, is emerging in the rehabilitation field. A recent Cochrane review highlighted a potential benefit of the electromechanical and robot-assisted upper limb training in stroke patients [2]. In addition, robotic therapy can increase the efficiency of therapy, and therefore the accessibility to treatment [3].…”
Section: Introductionmentioning
confidence: 99%